Evaluation Study on Accelerated Irrigation Benefits Programme (AIBP) - Planning Commission (Planning Commission, 2010)
The Accelerated Irrigation Benefits Program (AIBP) was formulated in the year 1996 by the Government of India in order to provide financial assistance to States to complete various ongoing multipurpose and irrigation projects in the country so as to extend irrigation to more areas. Over a period of time, the scope of the programme has widened. Presently, Major, Medium and Extension, Renovation and Modernization (ERM) projects are eligible for Central Assistance under AIBP. The surface water minor irrigation schemes of Special Category States as well as such schemes satisfying specified criteria in Non-Special Category States are also eligible for Central Assistance under AIBP.
Programme Evaluation Organisation Planning Commission Government of India
Programme Evaluation Organisation Planning Commission Government of India